Pusa Vilayati Palak: A highly nutritious Spinach variety - Yadav, R K; Tomar, B S; Choudhary, H; Sumanlata, Sumanlata (Indian Horticulture, 2020)
New indigenously developed spinach variety Pusa Vilayati Palak is a prickly seeded variety having completely green succulent stem and leaves. Leaves along with stem is cooked as vegetable. Male and female both plants are vegetative type with vigorous and luxuriant in growth. Leaves of this variety are smooth, soft having pointed apex with slight serration at bottom and middle of the leaf. It is short duration crop and gives 2-3 cuttings. Being a short duration crop, it can be easily fitted in rice-wheat or other cropping systems for cultivation during winter. It is rich source of fibre and other nutrients, like ascorbic acid, iron, calcium etc. It is suitable for winter season for both plain and hilly areas. It gives an average green leaf yield of 12 t/ha.